The Implementation of Islamic Boarding School-Based Curriculum in Increasing Religious Moderation Values in Students at Mts Hidayatullah Pakisan Bondowoso - Zainul Arifin (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This research aims to describe and describe the internalization of Islamic boarding school-based curriculum in increasing the values of religious moderation in students at MTs Hidayatullah Pakisan Bondowoso. By using a descriptive qualitative research method with the type of case study research (Case Study). This research used purposive sampling techniques, with techniques, in-depth interviews, participatory observation, and document analysis. Miles Hubberman's data analysis technique model, namely data collection, data reduction, data display, and data verification. Meanwhile, data presentation ensures the validity of the data by using data triangulation and source and method triangulation. The results of research on the internalization of Islamic boarding school-based curriculum in increasing the values of religious moderation in students at MTs Hidayatullah Pakisan Bondowoso illustrate that the implementation of the curriculum system itself which is based on Islamic boarding school values is proven by the existence of educational objectives, educational content, learning methods, learning evaluation, educational resources, educational organization and management, curriculum evaluation are all based on Islamic boarding schools. With steps to increase the values of religious moderation in students at MTs Hidayatullah Pakisan Bondowoso, namely inclusive religious education, promotion of tolerance and respect for differences, extracurricular activities, the presence of coaches and motivators, mentoring and training, positive behavior from madrasah leaders, education about religious dialogue, parental involvement, evaluation and feedback. Benefits that can be improved for students are having character, scientific values, honest and commendable nature, pleasant behavior and an offering attitude, friendly, gentle and polite, mutual respect, kinship and familiarity, harmony and togetherness in differences and has a strong sense of nationalism.